Attitude towards advertising from the perspectives of two (2) generational cohorts - Lim, Wui Kit (Universiti Malaysia Sarawak (UNIMAS), 2013)
The focus of this study is to determine the attitudes towards advertising from the perspective of two (2) generational cohorts. The study intend to analyze the belief affecting consumer' attitude towards advertising of the product by looking into factors such as product information, social role and image, falsity no sense, corrupt value and materialisrV Survey questionnaire is utilized as the instrument for data collection. The design of this study is in the form of cross-sectional quantitative research suitable for attitude towards advertising and marketing research. Respondents who under to this prospective-pursuer (21-34) group and social-striver (35-50) group located in Sarawak were selected to participate in this study which involved a total of 404 respondents. T-test is use to test the different belief between prospective-pursuers and social-strivers about advertising of beliefs. Regression is used to determine the effect of independent variables with dependent variable for each cohort. This study found out there is a significant difference between prospective-pursuer and social-striver about advertising of beliefs (product information, falsity no sense; corrupt value and materialism). Product information and social role and image had found that significant effect on attitude towards advertising to both generational cohorts. The interesting of the finding in this study about the corrupt value is also significant effect to attitude towards advertising to social-striver. The findings also suggested few recommendations for marketers and businesses to plan for their strategies to target the segment in Sarawak.